The microbial ecology of biltong in South Africa during production and at point -of-sale - Naidoo, Keshia (My University, 2010)
The aim of this work was to determine the microbial ecology of Biltong, a South African national snack commodity at point-of-sale and during production. It was established that biltong at point-of-sale carried bacterial counts ranging from ca. 6- 7 Log CFU/ g of aerobic mesophilic, ca. 2.5- 4 Log CFU/ g of Enterobacteriaceae, ca. 1.5- 3 Log CFU/ g of coliforms, ca. 1- 3 Log CFU/ g of presumptive Staphylococcus and ca. 1 Log CFU/ g of Escherichia coli populations in descending order. Furthermore, foodborne pathogens such as Listeria monocytogenes, Shigella dysenteriae and enterotoxin-producing Staphylococcus aureus were prevalent in low incidences (0.5- 2 %) in biltong product at point-of-sale and highlighted the potential of biltong as a reservoir for potential foodborne pathogens. It was shown that the type of biltong preparation method utilised in the production of biltong significantly influenced the survival of potential foodborne pathogens on the final product. In particular, enterotoxin-producing Staphylococcus strains were shown to survive throughout. Although, processing had a significant effect on the survival of bacterial pathogens on biltong product, the environment and conditions employed at point-ofsale further contributed to cross-contamination of biltong product prior to consumption.